Examining influential factors of academic dishonesty and ethical decision-making among community college nursing students - Lemon-Howard, Roshelle; Bista, Krishna; Gaulee, Uttam (American Journal of STEM Education, 2025)
This study investigates the relationship between factors influencing academic dishonesty and ethical decision-making among nursing students in Maryland community colleges. Using a cross-sectional survey, data were collected from 234 associate degree nursing students across three institutions. Results revealed a significant correlation between attitudes toward academic dishonesty and ethical decision-making, with ethical patterns increasing alongside lenient attitudes toward dishonesty. Differences were observed in ethical decision-making based on gender, semester level, and employment in healthcare. Findings highlight the importance of exploring the influence of familiarity with the American Nurses Association's Code of Ethics and faculty role modeling on ethical decision-making and dishonesty. The study underscores the need for further research to develop strategies for fostering ethical integrity among nursing students.